INTERNATIONAL EXPERIENCE OF ENVIRONMENTAL FACTORS ACCOUNTING IN ADJUSTING MACROECONOMIC INDICATORS - A. Abroskin; N. Abroskina (Вестник университета, 2019)
New requirements to the system of macroeconomic indicators, corresponding to the concept of socio-economic development sustainability, have been determined. The factors, associated with the features of gross domestic product constructing methodology, determining the trends observed in international statistics for adjusting or replacing the gross domestic product with other analytical indicators, have been identified. Actual problems of environmental factors accounting in the construction of adjusted gross domestic product values have been considered. The basic schemes for constructing gross domestic product modified versions used in modern international statistics have been presented. Approaches to the reflection of environmental components in the System of National Accounts have been systematized. International experience of environmental factors accounting in adjusting macroeconomic indicators has been codified. Recommendations on the use of advanced international experience in accounting for environmental factors in Russian statistics have been presented.